Chronic larval exposure to thiacloprid impairs honeybee antennal selectivity, learning and memory performances - Ke, Li; Chen, Xiasang; Dai, Pingli; Liu, Yong-Jun (Frontiers in Physiology, 2023)
The use of agricultural neonicotinoid insecticides has been shown to result in sub-lethal chronic effects that are more prevalent than acute toxicity to bees. Among these insecticides, thiacloprid, a commonly used low-toxic, has garnered significant attention due to its potential impact on the olfactory and learning abilities of honeybees. The effect of sub-lethal larval exposure to thiacloprid on the antennal activity of adult honeybees (Apis mellifera L.) have yet to be fully understood. To address this knowledge gap, laboratory-based experiments were conducted in which honeybee larvae were administered thiacloprid (0.5 mg/L, 1 mg/L). Using electroantennography (EAG), the impact of thiacloprid exposure on the antennal selectivity to common floral volatiles were evaluated. Additionally, the effect of sub-lethal exposure on odor-related learning and memory were assessed. The results of this study reveal, for the first time, that sub-lethal exposure to thiacloprid, when administered as larvae, prominently decreased honeybee antenna EAG responses to floral scents, leading to increased olfactory selectivity in the high dose 1 mg/L group compared to the control (0 mg/L VS. 1.0 mg/L: p< 0.05). Additionally, the results suggest that thiacloprid negatively affected odor-associated paired learning acquisition, as well as medium-term (1 h) (0 mg/L VS. 1.0mg/L: P = 0.019) and long-term memory (24 h) (0 mg/L VS. 1.0mg/L: P = 0.037) in adult honeybee. EAG amplitudes were dramatically reduced following R-linalool paired olfactory training (0 mg/L VS. 1.0mg/L: P = 0.001; 0 mg/L VS. 0.5mg/L: P = 0.027), while antennal activities were only significantly different in the control between paired and unpaired groups. Our results indicate that exposure to sub-lethal concentrations of thiacloprid can potentially affect honeybees' olfactory perception, as well as their learning and memory behaviors. These findings have important implications for the safe use of agrochemicals in the environment.